Design and the Question of Contemporary Aesthetic Experiences. Issue 2 (3rd July 2017) - Folkmann, Mads Nygaard; Jensen, Hans-Christian
Abstract: The article raises the question of the historical relativism of aesthetic experiences and argues that aesthetic experiences have changed according to new conditions in the contemporary age of globalization, mediatization and consumer culture. In this context, design gains attention as a primary case for aesthetic evaluation as design objects are, more than ever, framed and staged to be experienced aesthetically. Basing on this starting point, the article argues that an understanding of contemporary aesthetic experiences requires a meeting of cultural theory and philosophical approaches. On the one hand, cultural theory is required to understand the changed conditions of the production, circulation and consumption of aesthetic meaning in cultural forms of art and design. On the other, philosophical aesthetics gives access to understanding the mechanisms of aesthetic judgments and how they base on specific categories. It is a central argument of the article that aesthetic judgments are not only operators of ahistorical epistemology, but are culturally produced as well. The article discusses the question of contemporary aesthetic experiences through three questions: the role of aesthetic judgments, the role of aesthetic categories and the role of design in the case of a pair of TMA-2 headphones.